Chinese Anti-Rightist Campaign (1957-) - Sun, Warren (China Journal, 2011)
A review is presented for the “Chinese Anti-Rightist Campaign (1957-)” CD-ROM database, edited by the Editorial Board of the Chinese Anti-Rightist Campaign CD-ROM Database and produced by the Chinese University of Hong Kong.